Preparation and characterization of magnetic nanoparticles loaded with antimicrobial agent - Kanza Amjad; Muhammad Naeem Aamir; Muhammad Akram Choohan; Ume Habiba; Saif Ur Rehman (AMMANIF, 2022)
Background: Bacterial infections are an important cause of serious health issues worldwide. Various antibacterial drugs have been developed but they have numerous side effects. Development of drug loaded magnetic nanoparticles will help to achieve targeted drug delivery while sustaining the release of drug. It will also enhance its antibacterial activity by using iron oxide. Method: Drug loaded iron oxide nanoparticles were developed to sustain and enhance the antibacterial activity of drug. Chitosan was used as a polymer. The method adopted to prepare magnetic nanoparticles was co-precipitation. Formulated magnetic nanoparticles were tested for drug release, surface morphology, antibacterial activity and FTIR. Results: It was observed from the findings that both formulations were effectively loaded with drugs. It was also found that the release of drug levofloxacin was sustained over a period of 48 hrs. The SEM results showed the semi spherical nanoparticles effectively loaded with drug. FTIR spectrum revealed characteristic peaks related to functional groups. Raman spectroscopy showed characteristic bands of both drugs and drug loaded iron oxide nanoparticles. Antibacterial assay results showed an enhanced antibacterial activity by using iron oxide nanoparticles Conclusion: It was concluded from the study that magnetic nanoparticles could be one of the best approaches to load antibacterial drugs while sustaining and enhancing their antibacterial activity